PENGARUH CONTROL ORIENTED SEBAGAI STRATEGY MANAGEMENT ACCOUNTING TECHNIQUES TERHADAP COMPETITIVE ADVANTAGE DAN ORGANIZATIONAL PERFORMANCE - Rany, Arnius (Business Accounting Review, 2015)
The purpose of this study was to know the affect ofÂ  Control Oriented as a Strategy Management Accounting Techniques on Competitive Advantage and Organizational Performance in a company. In this study primary data was used by distributing questionnaires to companies that ware openly or closely which is engaged in manufacturing in Surabaya and Sidoarjo. This study used path modeling analysis technique with PLS tools. The result showed that the affect of Control Oriented on Competitive Advantage were positive and significant. In addition, the results also proved that there were positive and significant affect of Control Oriented on Organizational Performance, and also positive and significant affect of Competitive Advantage on Organizational Performance in companies engaged in manufacturing in Surabaya and Sidoarjo..